2023
DOI: 10.1097/md.0000000000034178
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Yiqi Huoxue Huatan recipe in the treatment of coronary atherosclerotic disease through network pharmacology and experiments

Abstract: In recent years, with population aging and economic development, morbidity and mortality of atherosclerotic cardiovascular disease associated with atherosclerosis (AS) have gradually increased. In this study, a combination of network pharmacology and experimental verification was used to systematically explore the action mechanism of Yiqi Huoxue Huatan Recipe (YHHR) in the treatment of coronary atherosclerotic heart disease (CAD). We searched and screened the active ingredients of Coptis chinensis, Astragalus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…JCR classifications and impact factors (IFs) for journals in 2023 were obtained, as well as H-indexes for countries, institutions, and researchers through the Web of Science database. The “Bibliometrix” package of R software was used for data analysis and graphical plotting, Scimago Graphica ( Hassan-Montero et al, 2022 ) 1 for global geo-visualization of publications, and ChiPlot ( Huang H. T. et al, 2023 ) 2 for plotting the distribution of keyword years.…”
Section: Methodsmentioning
confidence: 99%
“…JCR classifications and impact factors (IFs) for journals in 2023 were obtained, as well as H-indexes for countries, institutions, and researchers through the Web of Science database. The “Bibliometrix” package of R software was used for data analysis and graphical plotting, Scimago Graphica ( Hassan-Montero et al, 2022 ) 1 for global geo-visualization of publications, and ChiPlot ( Huang H. T. et al, 2023 ) 2 for plotting the distribution of keyword years.…”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies have demonstrated the anti-inflammatory and anti-AS effects and mechanisms of YHHR. [25][26][27][28] However, no study has yet demonstrated the effect of YHHR on AS through GM. In this paper, the correlation of YHHR and its main components with GM and AS was summarized to provide a reference for further study of traditional Chinese medicine and the development of innovative traditional Chinese medicine targeting GM.…”
Section: Project Within Budget Of Shanghai University Of Traditional ...mentioning
confidence: 99%